Inteligencia emocional y satisfacción laboral en docentes de educación inicial de la Red N° 4 de Ventanilla - Callao - Coca Guadalupe, Karina Tania (2010)
This study attempted to determine the relationship between Emotional Quotient and the level of job satisfaction in early education teachers in the network window No. 4 of the Callao Region. Type a descriptive correlation design and the sample consisted of 28 teachers who were administered the Job Satisfaction Scale (SL - SPC) and the Inventory of Emotional Intelligence ICE - BarOn; standardized by Nelly Ugarriza in Peru. The result of study shows that there is a low positive correlation 0.255 between the two variables, however in the analysis of the sub domains of emotional intelligence was found that both empathy and reality testing are significantly related to level job satisfaction.